The Influence of Self-Compassion and Mindfulness on Nurses’ Caring Behavior - Andi Ibrahim; Habibah Habibah (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the effect of capital structure, profitability, and firm size on firm value at PT Tiga Pilar Sejahtera Food Tbk during the period 2015–2024. The research employs a quantitative approach using secondary data obtained from the company’s annual financial statements. Data were analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, classical assumption tests were conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that capital structure has a positive and significant effect on firm value. Meanwhile, profitability and firm size do not have a significant effect on firm value. Simultaneously, capital structure, profitability, and firm size do not significantly affect firm value. These findings indicate that the explanatory power of the regression model is limited, which may be influenced by the relatively small sample size and the presence of other factors outside the research model that affect firm value.